Measuring plantar load with STAMPS3D: a preliminary study on the impact of contoured orthoses - Sairally, Francesca; Russell, David A.; Siddle, Heidi J.; Chauhan, Kate; Trinca, Daniele; Brockett, Claire; Culmer, Pete (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionDiabetes-related foot disease including foot ulcers (DFU) are a growing concern with a huge associated socio-economic impact. Bespoke contoured orthoses are a common clinical intervention used to help prevent DFU formation in regions at risk through offloading, by implementing various design features such as arch support, cuts-outs, metatarsal pads and variable density materials. Research surrounding contoured orthoses has been limited to measuring plantar pressure to assess effectiveness and guide insole modifications necessary for individual patients. However, there is currently no in-shoe measurement tool capable of measuring all components of plantar load (plantar pressure and shear stresses).MethodsThe STAMPS3D system has been developed to address this gap and has been successfully shown to measure the cumulative effect of plantar strain indicative of pressure and shear stresses that arise at the plantar interface. In this work, the STAMPS3D system has been used in a proof-of-concept study to explore the efficacy of capturing 3D strain data across a non-planar surface of different contoured orthoses.ResultsPlantar strain patterns were shown to vary across anatomical regions of the foot, with statistically significant increases in plantar strain found for contoured conditions across the midfoot due to offloading associated with contoured orthoses. Differences in plantar strain were also observed across the toe and forefoot regions as a result of changing the material stiffness of the orthoses.DiscussionThis work demonstrates the utility of employing 3D measurement to improve our understanding of plantar load under the influence of design features implemented in contoured orthoses and their ability to offload regions at risk of DFU formation. In doing so, improvements in management and prevention of diabetes-related ulceration can be made, tackling the social and financial costs associated.